1993
DOI: 10.1210/endo.133.6.8243291
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen alters the effects of neuropeptide-Y on luteinizing hormone and follicle-stimulating hormone release in female rats at the level of the anterior pituitary gland.

Abstract: In recent years, several studies have shown that neuropeptide-Y (NPY) is involved in the control of LH secretion. We determined the effects of estrogen on NPY-induced LH and FSH release in the absence or presence of LH-releasing hormone (LHRH) at the level of the anterior pituitary gland (APG). Adult female rats were ovariectomized. Fifteen to 20 days later, they were given a blank or estrogen-filled capsule subdermally and killed 17-19 h later. APG cells were isolated and cultured for 3 days in medium contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Similarly, NPY has been shown to have effects on LH release in vitro that are dependent on gonadal steroid milieu (23,24). The opposite effects of orexin A on the HPG at the pituitary and hypothalamus are not unusual and have been reported for other peptides (25).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, NPY has been shown to have effects on LH release in vitro that are dependent on gonadal steroid milieu (23,24). The opposite effects of orexin A on the HPG at the pituitary and hypothalamus are not unusual and have been reported for other peptides (25).…”
Section: Discussionmentioning
confidence: 86%
“…The suppression of basal LH levels by fasting fails in NPY knockout mice (208). However, pharmacological studies in rodents and primates (106,494) have suggested that the NPY has a dual action on the HPG axis according to sex steroids milieu. NPY has suppressive effects on LH pulse amplitude and frequency when sex steroids are low and a robust activational effect following steroid replacement in gonadectomized rats (38,106,301).…”
Section: Integrative Sites and Neuronal Networkmentioning
confidence: 99%